No influence of Indy on lifespan in Drosophila after correction for genetic and cytoplasmic background effects. - Janne M Toivonen; Glenda A Walker; Pedro Martinez-Diaz; Ivana Bjedov; Yasmine Driege; Howard T Jacobs; David Gems; Linda Partridge (PLoS Genetics)
To investigate whether alterations in mitochondrial metabolism affect longevity in Drosophila melanogaster, we studied lifespan in various single gene mutants, using inbred and outbred genetic backgrounds. As positive controls we included the two most intensively studied mutants of Indy, which encodes a Drosophila Krebs cycle intermediate transporter. It has been reported that flies heterozygous for these Indy mutations, which lie outside the coding region, show almost a doubling of lifespan. We report that only one of the two mutants lowers mRNA levels, implying that the lifespan extension observed is not attributable to the Indy mutations themselves. Moreover, neither Indy mutation extended lifespan in female flies in any genetic background tested. In the original genetic background, only the Indy mutation associated with altered RNA expression extended lifespan in male flies. However, this effect was abolished by backcrossing into standard outbred genetic backgrounds, and was associated with an unidentified locus on the X chromosome. The original Indy line with long-lived males is infected by the cytoplasmic symbiont Wolbachia, and the longevity of Indy males disappeared after tetracycline clearance of this endosymbiont. These findings underscore the critical importance of standardisation of genetic background and of cytoplasm in genetic studies of lifespan, and show that the lifespan extension previously claimed for Indy mutants was entirely attributable to confounding variation from these two sources. In addition, we saw no effects on lifespan of expression knockdown of the Indy orthologues nac-2 and nac-3 in the nematode Caenorhabditis elegans.